METHODOLOGICAL APPROACHES AND EXPERIENCE OF DEVELOPMENT THE STRATEGY OF SOCIO-ECONOMIC DEVELOPMENT OF LOCAL TERRITORIES (IN THE CASE OF THE KOZIN COMMUNITY) IN THE RIVEN REGION - Lyko, Dariia; Lyko, Serhii; Martyniuk, Vitalii; Portukhaі, Oksana; Yakuta, Olha (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The algorithm-chart of the development of the socio-economic development of the local area is illustrated and described on the example of the Kozinsky United Territorial Community (UTC), which includes four successive and interconnected blocks: cadastreregistration estimation, the actual model of sustainable development of the local area, SWOT-analysis and a cluster development strategy. During realization of cadastre-registration estimation of the united territorial community, the demographic situation, the labor market, the state of infrastructure development, natural resource potential, the ecological state of the territory and the presence of nature protection objects are reviewed and analyzed. According to the results of the SWOT-analysis, SWOT-matrices were constructed, which allowed to identify the relationships between «internal» (strengths and weaknesses) and «external» (opportunities and threats) factors that are of strategic importance to Kozinsk UTC. The cluster model of community development is proposed, which includes formation of agro-industrial (fruit and vegetable, grain, meat and dairy) and educational-educational clusters.